Informal Employment in Indonesia - Sining Cuevas; Christian Mina; Marissa Barcenas; Aleli Rosario (Asian Development Bank (ADB), 2009)
The paper attempted to use the February 2007 round of Indonesia's National Labor Force Survey (Sakernas) for a comparative analysis of wages and benefits of formal and informal workers. While Sakernas was not designed for this purpose, the study explored questions in the existing survey that can be used to distinguish formal and informal workers. Because of data limitation, workers were classified as employed informally or "mixed" - a category composed of workers who cannot be identified, with precision, to be engaged in either formal or informal employment. Given this constraint, informal employment was estimated at the minimum to be at 29.1% of total employment in Indonesia. Informal employment is also highly concentrated in rural areas and is prevalent in agriculture and construction sectors. More women are likely to be informally employed than men, and women generally receive lower pay and are mostly unpaid family workers. To the extent possible the study was able to examine informal employment in Indonesia and to identify the gaps in the Sakernas questionnaire that can be addressed in future rounds of the survey for a successful comparative analysis between formal and informal workers.
hdl:11540/1805
Keywords: 330; Indonesia; informal employment; informal sector; gender analysis; wage differentials; Erwerbstätigkeit; Informelle Wirtschaft; Indonesien